7 - PRODUCTION OF SURGICAL BIOMODELS TO SUPPORT SURGERY BY 3D PRINTING: A SOCIAL AND ECONOMIC EVALUATION FROM THE DESIGN FOR SUSTAINABILITY PERSPECTIVE - Claudio Pereira de Sampaio; Sonia Maria Fabris Luiz; José Antonio Vicentin; Glaykon Alex Vitti Stabile; Cecília Luiz Pereira Stabile (Mix Sustentável, 2024)
This article presents, describes, and evaluates, from the perspective of Design for Sustainability (DfS), the social, economic, and technological aspects of the process of developing and manufacturing anatomical biomodels to support surgery using 3D printing in a Brazilian public hospital. This process had an interdisciplinary character, involving professionals of Design, Odontology, and Physiotherapy. The assessment was carried out using DfS (Design for Sustainability) social and environmental heuristics (guidelines), and enabled the identification of relevant aspects, as well as opportunities for improvement in processes. Among the results, the importance of having a specific space dedicated to digital manufacturing in public hospitals stands out, which speeds up the development of biomodels, as well as the quantity, diversity, and quality of 3D printing equipment, which allows the exploration of multiple possibilities for processes and materials, speeding up innovation in the hospital environment.